Evaluation and Revision of Standard Operating Procedure of Cleaning in the Production of Condensed Sweetened Milk of a Particular Company - Sukardi, Sukardi; T., Retno Astuti; Dianasari, R. (Jurnal Teknologi Pertanian, 2007)
This study was conducted to evaluate the Standard Operating Procedure (SOP) of the cleaning process, particularly the manual cleaning in the production of condensed sweetened milk of a particular company. A descriptive method of analysis was used in the study. Aspects evaluated were cleaning time, methods, tools and the cleaning steps. The works were focused on two processing steps, namely filling and squeezeable bottling machines. The SOP of manual cleaning in the filling step was well implemented and the data were fully documented and therefore may be evaluated.Â The study suggested that some improvement of SOP for manual cleaning was needed, especially on the cleaning of filling machines Ferrum 24 and 28 and for the FMC. It was recommended to schedule and to time the cleaning. It was also necessary to improve the cleaning method and to use Bahasa Indonesia for the SOP. The use of picture or photographs for the SOP of cleaning steps will be very helpful. On the other hand, the SOP of the squeezeable bottling machine was considered to be appropriate enough and therefore no improvement was required.Keywords: evaluation, SOP, cleaning